2021
DOI: 10.1097/mbp.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on blood pressure response to exercise in a severely obese population

Abstract: Background Exaggerated blood pressure response to exercise is a cardiovascular risk factor associated to higher morbidity and mortality. Severely obese patients have an increased risk of exercise-induced hypertension (EIH). We aimed to assess the blood pressure response to exercise in patients with severe obesity who underwent bariatric surgery as well as the main determinants of this response. Methods We used data from the ACTIVE clinical trial, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Proposed pathophysiological mechanisms and clinical correlates of EBPR include familial predisposition to hypertension, endothelial dysfunction, impaired arterial baroreflex sensitivity, abnormal neurohormonal response to exercise, large artery stiffness, male gender, pre-hypertension, comorbidities such as obesity, diabetes, obstructive sleep apnea, and subclinical HMOD [ 33 , 34 , 35 , 36 , 37 , 38 ]. Over the last three decades, a large body of evidence has shown that all these factors, often associated, similarly also play a role in MH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed pathophysiological mechanisms and clinical correlates of EBPR include familial predisposition to hypertension, endothelial dysfunction, impaired arterial baroreflex sensitivity, abnormal neurohormonal response to exercise, large artery stiffness, male gender, pre-hypertension, comorbidities such as obesity, diabetes, obstructive sleep apnea, and subclinical HMOD [ 33 , 34 , 35 , 36 , 37 , 38 ]. Over the last three decades, a large body of evidence has shown that all these factors, often associated, similarly also play a role in MH.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies aimed at investigating clinical correlates of MH reported that male gender, older age, high normal office BP, active smoking, excessive alcohol drinking, obesity, metabolic syndrome, job stress, and sleep apnea syndrome are major factors responsible of out-of-office hypertension in clinically normotensive individuals. For instance, participants with MH in the Pensioni Arteriose Monitorate e Loro Associazioni (PAMELA) study [ 37 ] showed a greater male prevalence, age, BMI, office and 24 h heart rate, and office and 24 h mean SBP/DBP compared to participants with true normotension [ 39 ]. In contrast, our meta-analysis revealed that participants with MH had similar clinical features as normotensives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the insulin sensitizer rosiglitazone has been reported to play a beneficial effect on resting BP as well as on BP response to exercise in men with type 2 diabetes mellitus and coronary artery disease, especially in those with EBPR [ 73 ]. Finally, weight loss after bariatric surgery, a treatment increasingly used in morbid obesity, has been shown to effectively reduce the high prevalence of EBPR in these patients [ 74 ]. It is worth mentioning, however, that evidence on the effects of non-pharmacological and pharmacological interventions on CV outcomes in patients with EBPR is still lacking.…”
Section: Clinical Managementmentioning
confidence: 99%